2021
DOI: 10.1093/jac/dkab039
|View full text |Cite
|
Sign up to set email alerts
|

Invasive infections withPurpureocillium lilacinum: clinical characteristics and outcome of 101 cases from FungiScope® and the literature

Abstract: Objectives To provide a basis for clinical management decisions in Purpureocillium lilacinum infection. Methods Unpublished cases of invasive P. lilacinum infection from the FungiScope® registry and all cases reported in the literature were analysed. Results We identified 101 cases with invasive P. lilacinum infection. Main predisposing factors were haematolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
6

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(57 citation statements)
references
References 33 publications
4
47
0
6
Order By: Relevance
“… 1–5 As shown in Figure 5a and Figure S7, the bacterial translocation markers (lipoteichoic acid, LTA and lipopolysaccharide binding protein, LBP) and monocyte activation marker (soluble CD14, sCD14), which are metabolically related, clustered together and directly correlated with Purpureocillium lilacinum (r = 0.86, 0.72, 0.82, respectively), a filamentous fungus able to produce opportunistic infections in immunocompetent and immunocompromised hosts. 23 Also, bacterial members, such as Blautia, Streptococcus, Romboutsia , and Lachnospiraceae genus, showed a correlation with these three inflammation markers (Table S5), as previously reported. 21 , 22 Other correlations included a direct association between soluble CD163 (sCD163), a biomarker of macrophage activation, with lower association index with Purpureocillium lilacinum (r = 0.39), Romboutsia (r = 0.44) and Lachnospiraceae UCG-004 (r = 0.39) although they showed lower association index (Figure S7, Table S5).…”
Section: Resultssupporting
confidence: 84%
“… 1–5 As shown in Figure 5a and Figure S7, the bacterial translocation markers (lipoteichoic acid, LTA and lipopolysaccharide binding protein, LBP) and monocyte activation marker (soluble CD14, sCD14), which are metabolically related, clustered together and directly correlated with Purpureocillium lilacinum (r = 0.86, 0.72, 0.82, respectively), a filamentous fungus able to produce opportunistic infections in immunocompetent and immunocompromised hosts. 23 Also, bacterial members, such as Blautia, Streptococcus, Romboutsia , and Lachnospiraceae genus, showed a correlation with these three inflammation markers (Table S5), as previously reported. 21 , 22 Other correlations included a direct association between soluble CD163 (sCD163), a biomarker of macrophage activation, with lower association index with Purpureocillium lilacinum (r = 0.39), Romboutsia (r = 0.44) and Lachnospiraceae UCG-004 (r = 0.39) although they showed lower association index (Figure S7, Table S5).…”
Section: Resultssupporting
confidence: 84%
“…Significant differences in in vitro antifungal susceptibility were observed between P. variotii sensu lato and P. lilacinum , which is consistent with the findings of other studies [ 4 , 5 , 6 , 8 , 13 , 14 , 15 ]. In general, the antifungal susceptibility profiles of P. variotii stricto sensu , P. maximus , P. dactylethromorphus , and P. divaricatus appeared to be similar to what other studies had already shown, although a limited number of isolates were tested in those studies [ 13 , 14 , 15 ].…”
Section: Discussionsupporting
confidence: 91%
“…Paecilomyces fungi often infect immunocompromised patients, however immunocompetent patients are not spared and can become infected by direct inoculation of the fungus following trauma. Clinical presentations of Paecilomyces spp., such as cutaneous or catheter-related infections, ocular infections, peritonitis, sinusitis, pneumonia, osteomyelitis or fungemia have been reported in the medical literature [ 3 , 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Its lilac obverse color and its characteristic to sporulate in infected tissues together help the identification of P lilacinum infections. 13,14 Species identification of the causative agent is crucial for treatment because different species of the genus Paecilomyces show variable susceptibilities to antifungal medicines. P lilacinum has a poor response to traditional antifungal agents.…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of P lilacinum infection is based on the culture of the fungus and pathology of the lesions. Its lilac obverse color and its characteristic to sporulate in infected tissues together help the identification of P lilacinum infections 13,14 …”
Section: Discussionmentioning
confidence: 99%